Environmental drivers and ecological implications of a ctenophore swarm: a case study from the Bay of Bengal, northern Indian Ocean - Alfisa Siddique; Aishee Bhowal; Jasmine Purushothaman; Rakhesh Madhusoodhanan; Dhriti Banerjee (Journal of Water and Climate Change, 2023)
Ctenophores are quick responders to coastal environmental changes and play a crucial role in marine food web dynamics. We report the environmental drivers of a ctenophore swarm (Pleurobrachia spp.) and associated ecological changes in estuarine and coastal waters of the Sundarbans mangrove–estuarine complex in the northern Bay of Bengal (BoB). Plankton and fish samples were collected from estuarine and coastal waters at the peak of estuarine outflow in the northeast monsoon (NEM). Sampling locations at the estuarine mouth witnessed ctenophores (Pleurobrachia pileus and  Pleurobrachia globosa) in swarming proportions. Multivariate statistical analysis revealed significant differences in hydrographical and biological properties between the swarm and non-swarm areas. The sea surface salinity, ammonium, and mesozooplankton (MSP) density were positively correlated while microzooplankton (MCZ) density was negatively correlated with the ctenophore swarm. Fish caught from swarm locations, dominated by microbial food web consisted of species of less market value, while those from the non-swarm locations, dominated by conventional plankton food web consisted mainly of commercially important species. Thus, in the first-ever record from a commercially important fishing ground in the BoB, this study provides evidence of how a ‘dead end’ plankton predator affects the plankton food web organization and fisheries in tropical coastal waters. HIGHLIGHTS Occurrence of a ctenophore swarm and its hydrobiological links investigated in the BoB.; The ctenophore swarm and non-swarm locations favoured different plankton trophic pathways.; Active ctenophore predation on copepods favoured the microbial loop in swarm locations.; Predation on swarm-forming ctenophore favoured the conventional food chain.; Ctenophore swarm negatively affected fish community composition.;